Country's Development Through Women Empowerment: The Initiatives taken by Government of Mizoram Through Central Government - Hmingchungnungi, Ruthi (Indian Journal of Political Science)
Education and economic development are essential for raising people's social status. A man may not be able to predict his future if he lacks education. However, pure education alone cannot guarantee a better future for everyone. As a result, economic development is also crucial. Women account for 48.46 percent of India's total population. If all of these women are not developed, the country will be unable to progress. Due to the society's rigid customs, women's conditions used to be at the depths of despair. The Indian government strives to improve the status of women in all areas, but it is unable to achieve much. Starting from 1980's the central government take initiatives for poverty reduction and women empowerment through different schemes. This paper will cover the different schemes and implementation made by the central and state government for women empowerment in Mizoram. - Reproduced
Keywords: women empowerment, Government of Mizoram, society development